Examination of Life Satisfaction in Youth and Sports Volunteers - Damla Özsoy, Turgay Biçer (Pakistan Journal of Medical & Health Sciences, 2022)
Background:Today, in industrial society, people may need beneficial activities to increase their physiological-psychological and emotional performances and contribute to their peaceful life. In this study, it is based on the research of life satisfaction of sports volunteers who take part in sports organizations voluntarily. Aim: In this study, it was aimed to investigate the life satisfaction of sports volunteers in terms of various variables. It is very important to determine the variables that affect people’s life satisfaction. Methods: Descriptive statistics method was used in this study, which aimed to examine the life satisfaction of youth and sports volunteers who took part in sports organizations in terms of various variables. The sample of the study consists of 390 sports volunteers selected by convenience sampling method. Life Satisfaction Scale adapted to Turkish by Akın & Yalnız (2015) was used. The life satisfaction of the sports volunteers who took part in the sports organization was examined in terms of various variables. The age range of the participants in the sample is 18-40. The sample of the study consists of 390 sports volunteers with 95% confidence and 5% error. The hypotheses of the obtained data were analyzed with the SPSS program. The statistical information of the participants was evaluated by using the descriptive survey method. First of all, the validity and reliability analysis of the scale was performed. The mean score of the scale was analyzed statistically. Research hypotheses were tested with Mann Whitney-U and Kruskall Wallis tests. Results: According to Mann Whitney-U Tests: While there was no difference in the life satisfaction of the participants according to the gender variables, according to the relationship status variable, the life satisfaction of the married participants was higher than the singles. Also, according to Kruskall Wallis Test: It was observed that as the education level of the participants increased, their life satisfaction increased. In addition, there was no difference according to their age classes. Conclusion: This sample group has undertaken these duties in order to produce a certain production in the society and to be useful individuals rather than life satisfaction, and they can get spiritual pleasures rather than material expectations related to age. Therefore, this group is likely to have higher levels of life satisfaction.